Immunotherapy in endometrial cancer: mechanisms, clinical evidence, and future directions - Lian, Mengyi; Zhang, Chengwei; Li, Tianye; Wang, Aiming (Frontiers in Immunology, 2026)
Endometrial cancer (EC) treatment has been revolutionized by the integration of immunotherapy, particularly for molecularly defined subsets of patients. The classification of EC into DNA polymerase epsilon-mutated (POLE-mutant), mismatch repair-deficient (dMMR), p53-abnormal, and no specific molecular profile (NSMP) subtypes provides a critical framework for predicting response to immune checkpoint blockade. dMMR and POLE-mutant tumors, with their hypermutated and immunogenic phenotypes, demonstrate exceptional sensitivity to Programmed Death-1(PD-1) inhibitors such as pembrolizumab and dostarlimab in clinical trials. In contrast, overcoming the immunoresistant nature of NSMP and p53-abnormal EC requires innovative combinations, exemplified by the success of pembrolizumab plus the multitargeted tyrosine kinase inhibitor lenvatinib. Recent practice-changing clinical trials have further established combination strategies incorporating PD-1 blockade with chemotherapy as a new first-line standard for advanced disease, marking a paradigm shift in the management of advanced EC. This review synthesizes the mechanistic basis for these approaches, the compelling clinical evidence supporting approved therapies, and the frontier of investigational strategies, including cellular therapies, novel immune checkpoints, and rational combination regimens—aimed at expanding the benefit of immunotherapy to a broader range of patients with EC.